ANALYSIS ON NEGATIVE TRANSFER OF â€œINDONESIANâ€ AS â€œSLâ€ INTO â€œENGLISHâ€ AS â€œFLâ€ - Wahyuni, Sri Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: This research is conducted to find out the type of grammatical interference and to describe the frequency of negative transfer made by Indonesian-speaking students in transferring Indonesian text into English text. The corpus was collected from Semester-2 students of English Study Program in Teacher Training and Education Faculty of Tanjungpura University in Academic Year 2016/2017. This was a descriptive study. The result shows that 265 grammatical errors were encountered from the corpus. They are categorized into 8 types of interlingual negative transfer, covering verb-tense forms, subject-verb agreements, word orders, prepositions, articles, pluralities, pronouns and auxiliaries. The percentage was found highest in verb-tense form by 38,5% or equals to 102 errors. Students’ grammatical errors in transferring Indonesian text into English text are highly influenced by their first or second language. Keywords: Analysis, Negative Transfer, Interlingual, Grammatical Error Abstrak: Penelitian ini dilakukan untuk mengetahui jenis gramatikal interferensi dan menggambarkan frekuensi transfer negatif oleh mahasiswa yang berbahasa Indonesia dalam mentransfer teks Indonesia ke dalam teks bahasa Inggris. Kumpulan tulisan diambil dari 12 siswa semester 2 dari Program Studi Bahasa Inggris di Fakultas Keguruan dan Ilmu Pendidikan di Universitas Tanjungpura pada Tahun Akademik 2016/2017. Ini merupakan penelitian deskriptif. Hasil menunjukkan sebanyak 265 kesalahan tata bahasa ditemukan di dalam kumpulan tulisan tersebut. Kesalahan-kesalahan tata bahasa itu dikategorikan menjadi 8 jenis transfer negatif interlingual, meliputi verb-tense forms, subject-verb agreements, word orders, prepositions, articles, pluralities, pronouns dan auxiliaries. Persentase kesalahan tertinggi adalah bentuk verb-tense dengan persentase error 38,5% atau setara dengan 102 kesalahan. Kesalahan tata bahasa siswa dalam mentransfer teks berbahasa Indonesia ke dalam Bahasa Inggris besar dipengaruhi oleh bahasa pertama atau kedua mereka. Kata kunci: Analisis, Transfer Negatif, Interlingual, Kesalahan Gramatikal